PENGARUH PENERAPAN METODE DRILL DENGAN PENDEKATAN OPEN-ENDED TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP PERTI PADANG TAHUN PELAJARAN 2013/2014 - Putra, Roni; Rismen, Sefna; Edriati, Sofia (STKIP PGRI Sumbar, 2014)
ABSTRACTThe research was based by low studentsâ comprehension of mathematical concept, Â Lack of motivation student in course of learnings, energy natural existense and imagination child still low and also student tardy and difficult in comprehension lesson. Target of research this was to know studentsâ comprehension of mathematical concept which process studying implementing drill method with approach open ended better than study conventional. This was an experimental research which used random. Hypothesis test used t-test one way with MINITAB software obtained that tvalue= 2,15 and ttable= 1,67 with Î± = 0,05. Because of Â > then H0 was rejected. It can be conclude that studentsâ comprehension of mathematical concept by implementing drill method with approach open ended was better than studentsâ comprehension concept of mathematical concept by implementing conventional in class VIII SMP PERTI Padang.